2010
DOI: 10.1021/es903502g
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Naphthalenes (PCNs): Congener Specific Analysis, Occurrence in Food, and Dietary Exposure in the UK

Abstract: Information on the occurrence of toxicologically significant polychlorinated naphthalenes (PCNs) in food, or on human exposure, is sparse. In this work, PCN congeners (PCNs 52, 53, 66/67, 68, 69, 71/72, 73, 74, and 75) were selected for analysis, based on the available literature on current occurrence and toxicology, and limited by the commercial availability of reference standards. The analytical methodology used cold solvent extraction of prehydrolyzed samples fortified with internal standards ((13)C(10) lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 22 publications
5
69
0
Order By: Relevance
“…Foods that were subject to some measure of processing (oils, cereals, meat etc.) and fish showed highest levels of PCNs [22,23]. Thus, it is not surprising that PCNs have been found in humans and wildlife.…”
Section: Animalsmentioning
confidence: 98%
“…Foods that were subject to some measure of processing (oils, cereals, meat etc.) and fish showed highest levels of PCNs [22,23]. Thus, it is not surprising that PCNs have been found in humans and wildlife.…”
Section: Animalsmentioning
confidence: 98%
“…A full description of the reagents, reference standards and procedures used for the extraction and analysis of PCNs has been reported by Fernandes et al [18]. In brief, samples were fortified with 13 C-labelled analogues of target compounds and exhaustively extracted using mixed organic solvents.…”
Section: Polychlorinated Napthalenes (Pcns)mentioning
confidence: 99%
“…The quality control criteria used for evaluating data are very similar to the accredited methodology used for the chlorinated dioxins and PCBs [18]. There are no available RMs specific to PCNs, but the same material used for PCDD/F and PCB analysis (cod liver oil) was analysed during the course of this work with results showing good consistency and agreement with established values.…”
Section: Polychlorinated Napthalenes (Pcns)mentioning
confidence: 99%
“…The occurrence of PCNs in the environment, and human exposure to them, have caused an increasing amount of public attention, and PCNs in aquatic animals and human dietary exposure have been reviewed several times (Falandysz, 2003;Domingo, 2004;Fernandes et al, 2010). PCN concentrations have also been measured in various environmental matrices in a number of regions (Jarnberg et al, 1997(Jarnberg et al, , 1999Krauss and Wilcke, 2003;Helm et al, 2004;Jaward et al, 2004;Herbert et al, 2005;Lee et al, 2007;Ishaq et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The PCN TEQ in biota from polar environments accounts for about 10% or more of the sum of the PCDD/F, dioxin-like PCB, and PCN TEQs (Bidleman et al, 2010). Human exposure to PCNs and concentrations in human fat have been investigated in a number of regions (MartiCid et al, 2008;Fernandes et al, 2010;Horii et al, 2010;Schiavone et al, 2010), and, in a recent study, Park et al found that the PCN TEQs in some human serum samples, calculated using the TEFs reported by Puzyn et al (2007), were comparable with the PCDD/F and PCB TEQs (Park et al, 2010). Furthermore, the authors suggested that industries that involve thermal processes might be PCN sources to humans, because of the PCN profiles found in the serum samples (Park et al, 2010).…”
Section: Introductionmentioning
confidence: 99%